Chapter 25 Normative, Empiricist, and Interpretive Considerations in the Ageism Research Process (2018)
This chapter reflects on the normative, empiricist, and interpretive considerations researchers face in the process of researching ageism. The chapter is based on a doctoral dissertation that triangulated data, methods, and theory to explore how ageism is manifested and sustained in the lives of older people. Little attention has previously been devoted to the philosophy of science aspects explicitly related to ageism. An increasing number of ageism publications report on empirical data, but these publications are rarely explicitly related to epistemological and ontological questions. Consequently, there is a gap in what we know about the wide scope of challenges in researching ageism and in how we view and understand ageism in our world. Focusing on the different types of considerations researchers face is a way to show how the choices we are forced to make in the process enable us to or prevent us from making claims about the phenomenon of ageism. Delving into a wider study of epistemological and ontological questions while simultaneously examining ageism definitions and studies can hopefully guide future researchers to make better informed choices on a variety of ways to do research on ageism. Overlapping normative, empiricist, and interpretive contexts can be a way to identify novel research questions, design studies triangularly, and enable new knowledge about ageism, its origins, consequences, and practices.